Correlation Analysis Of PM10 With Tropospheric Ozone (O3) During Forest And Land Fire Event In Sumatera - Ade Ayu Oktaviana; Alvin Pratama; Ikhsan Buyung Arifin; Joni Hermana (Jurnal Serambi Engineering, 2024)
Indonesia has a forest area of ​​120,495,702.96 hectares which is vital for human survival. However, significant forest fires, such as those in 1997/1998 and 2015, have caused widespread damage and impacted neighboring countries. These forest fires contribute to an increase in tropospheric ozone (O3) concentrations which are dangerous for human health. This study aims to evaluate the correlation between PM10 and tropospheric ozone in Sumatra during forest fires, using data from the Bukit Kototabang Global Atmospheric Monitoring Station. The analysis method involves measuring PM10 and O3 concentrations using the BAM1020 and Ozone Analyzer Model 49 I, as well as Pearson correlation and linear regression analysis. Results show that there is a positive correlation (r = 0.53) between PM10 and tropospheric ozone, with PM10 increasing as O3 concentrations increase during extreme conditions. The average monthly concentrations of PM10 and O3 during 2016-2020 were 21.75 µg/m3 and 11.61 ppb respectively, with peak concentrations of PM10 in September and O3 in February. Increases in PM10 during forest fires contribute to increases in ozone precursors and photochemical processes, accelerating the formation of tropospheric ozone.